Kinerja Jalan Beton Semen pada Lalu Lintas Bervolume Rendah di Indonesia - Dachlan, Tatang (Department of Civil Engineering, Diponegoro University, 2006)
This paper aimed to identify the performance of cement concrete roads pavement constructed on several low volume roads location This study is based on the design method from Cement Concrete Institute (CCI, 2000).Based on study in Pusat Litbang Prasarana Transportasi, this method may be used because relatively more simple and relatively effective and efficient for determining the thickness design of cement concrete road pavement for low volume traffic in Indonesia. In analyzing the performance of cement concrete road pavement located on predicted low volume roads category, field surveys are performed such as road surface condition, sampling by core drill, and bearing strength of road pavement courses using Dynamic Cone Penetrometer (DCP). The result may be identified that there are variable thickness based on existing data. This result may be considered in formulating the determination of design thickness of cement concrete pavement for low traffic roads in Indonesia.Keywords: cement concrete roads, low volume roadsPermalink: http://www.ejournal.undip.ac.id/index.php/mkts/article/view/3932[How to cite: Dachlan, T., 2006, Kinerja Jalan Beton Semen pada Lalu Lintas Bervolume Rendah di Indonesia, Jurnal Media Komunikasi Teknik Sipil, Volume 14, Nomor 1, pp. 30-47]